Cortical and subcortical JC virus infection: two unusual cases of AIDS associated progressive multifocal leukoencephalopathy. Issue 8 (August 1994) - Sweeney, B J; Manji, H; Miller, R F; Harrison, M J; Gray, F; Scaravilli, F
Abstract : Two patients with AIDS and progressive neurological syndromes had necropsies that identified JC virus infection of the cerebral or cerebellar cortex. The unusual presentation of progressive multifocal leukoencephalopathy with grey matter involvement and normal cerebral imaging is discussed.